2021
DOI: 10.1371/journal.pone.0251661
|View full text |Cite
|
Sign up to set email alerts
|

Real-life clinical sensitivity of SARS-CoV-2 RT-PCR test in symptomatic patients

Abstract: Background Understanding the false negative rates of SARS-CoV-2 RT-PCR testing is pivotal for the management of the COVID-19 pandemic and it has implications for patient management. Our aim was to determine the real-life clinical sensitivity of SARS-CoV-2 RT-PCR. Methods This population-based retrospective study was conducted in March–April 2020 in the Helsinki Capital Region, Finland. Adults who were clinically suspected of SARS-CoV-2 infection and underwent SARS-CoV-2 RT-PCR testing, with sufficient data i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…SARS-CoV-2 RNA test is the golden standard and the most commonly used method for diagnosing COVID-19 across guidelines and regulations, and in this study, all suspected cases and the contacts immediately underwent SARS-CoV-2 RNA testing by rRT-PCR assays of respiratory (throat swab and sputum) specimens, which are the most commonly recommended specimens across guidelines and regulations and which are more easily obtainable and more practicable. A Finland population-based study showed that the clinical sensitivity of SARS-CoV-2 RT-PCR testing was only moderate at best, with relatively high false-negative rates (26), and a single swab test might not be sufficient (27); the sensitivity was even lower among smokers (28). Test sensitivity increased with more test times, and were 72.4, 89.8, 97.3, and 100.0% for the first, second, third, and seventh tests, respectively (22).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 RNA test is the golden standard and the most commonly used method for diagnosing COVID-19 across guidelines and regulations, and in this study, all suspected cases and the contacts immediately underwent SARS-CoV-2 RNA testing by rRT-PCR assays of respiratory (throat swab and sputum) specimens, which are the most commonly recommended specimens across guidelines and regulations and which are more easily obtainable and more practicable. A Finland population-based study showed that the clinical sensitivity of SARS-CoV-2 RT-PCR testing was only moderate at best, with relatively high false-negative rates (26), and a single swab test might not be sufficient (27); the sensitivity was even lower among smokers (28). Test sensitivity increased with more test times, and were 72.4, 89.8, 97.3, and 100.0% for the first, second, third, and seventh tests, respectively (22).…”
Section: Discussionmentioning
confidence: 99%
“…In early reports, the immature development of NAAT technology for SARS-CoV-2 detection can be blamed for the moderate clinical sensitivity of qRT-PCR assays (71–82.2%) [ 100–103 ]. However, after more than a year of intensive development and optimization, the clinical performance of qRT-PCR has not been markedly improved [ 104 ], especially for screening in population-based and hospital settings [ 105 , 106 ].…”
Section: Nucleic Acid Amplification Testing (Naat) Methodsmentioning
confidence: 99%
“…The RT-PCR test has been found to have varying sensitivities ranging from 28% to 85%. [9][10][11][12] This test is time consuming and false negative results are common within the first 7 days of infection and if the sample is not collected in the time period of viral replication or if the viral genome is missed. 13 As COVID-19 primarily targets the lungs, and due to inability of the RT-PCR to successfully diagnose all cases of COVID-19, it would appear that chest CT would play a crucial role in the diagnosis, evaluation and management of the disease.…”
Section: Original Researchmentioning
confidence: 99%